Establishing the applicability of the wiki technology in improving writing in English. - Tan, Bee Hoon (2012)
Students today are growing up with the Internet, and this has impacted on how they live and learn. Therefore, teachers can no longer rely solely on traditional pedagogy in English language instruction. More engaging techniques are needed to motivate learning. In English-as-Second-Language (ESL) contexts, students are often reluctant to write in English. Their reluctance can be attributed to the lack of a real or compelling reason to write, the absence of complementary support besides the teacher-fronted classroom, and the ignorance of interesting writing tools. Yet writing in English is an essential skill for students to succeed in their academic endeavours and later in their career. This observation instigated the present study to investigate the applicability of wiki for the teaching and learning of English, focusing especially on writing. This study explored the application of a Writing With Wiki (WWW) approach in both secondary and tertiary contexts where students were trained to use a Wiki tool to collaboratively write subject-related materials. The task motivated the students to write as they appreciated the authentic purpose of their writing. It also boosted students' confidence that they could be website or textbook writers, besides earning to be critical thinkers in evaluating and integrating related content in the materials they developed. The study affirmed the value of the WWW approach for English language teaching and learning.